2008
DOI: 10.1209/0295-5075/84/24001
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of large-scale circulation in turbulent rotating convection

Abstract: Turbulent rotating convection in a cylinder is investigated both numerically and experimentally at Rayleigh number Ra = 10 9 and Prandtl number σ = 6.4. In this Letter we discuss two topics: the breakdown under rotation of the domain-filling large-scale circulation (LSC) typical for confined convection, and the convective heat transfer through the fluid layer, expressed by the Nusselt number. The presence of the LSC is addressed for several rotation rates. For Rossby numbers Ro 1.2 no LSC is found (the Rossby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
129
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 26 publications
26
129
0
Order By: Relevance
“…Also shown are the DNS results from Ref. [15]; these data agree rather well with the experimental data at nearly the same Pr and Ra. One sees that the enhancement of Nu at large Ro is nearly independent of Pr, but as Ro decreases below unity a strong Pr dependence manifests itself.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Also shown are the DNS results from Ref. [15]; these data agree rather well with the experimental data at nearly the same Pr and Ra. One sees that the enhancement of Nu at large Ro is nearly independent of Pr, but as Ro decreases below unity a strong Pr dependence manifests itself.…”
supporting
confidence: 77%
“…However, at modest rotation rates, experiments [9][10][11] and numerical simulations [12][13][14][15] have shown that under certain conditions the heat transport can also be enhanced, before it rapidly decreases for stronger rotation. This enhancement has been ascribed to Ekman pumping [13,[16][17][18]: Because of the rotation, rising or falling plumes of hot or cold fluid are stretched into vertical vortices that suck fluid out of the thermal boundary layers (BL) adjacent to the bottom and top plates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a slight overshoot of rotating heat transfer beyond the RBC scalings for Ra Ra T (cf. Niiler & Bisshopp 1965; Julien et al 1996;Kunnen et al 2008). However, this effect is strong only at relatively high E. In fact, our data shows that the overshoot becomes small for E 10 −5 .…”
Section: Rotating Convectionmentioning
confidence: 50%
“…Previous experimental [7]- [13] and numerical studies [11]- [16] at constant Ra and Pr have shown that at moderate rotation rates the convective heat transfer is higher than for the nonrotating case. This heat transport enhancement with respect to the non-rotating case has been ascribed to Ekman pumping [8], [10]- [13], [15]- [18].…”
mentioning
confidence: 85%